Simply by expanding any brackets and collecting like terms

5x - 2 - 2x + 3

is this

5x - 2x = 3x

2 + 3 = 5

therefore 3x - 5

if wrong please explain

Thanks....

2 answers

5x-2x = 3x BUT
it's -2+3 = 1
therefore
3x+1
Thank you ..I see where I am making my mistake ..THANK YOU !!!!
Similar Questions
    1. answers icon 3 answers
  1. 21. When expanding the brackets (a - 2)2 will be:A. a2 - 4a + 4 B. a2 - 4 C. a2 + 4
    1. answers icon 1 answer
  2. 22. When expanding the brackets (x - 2)(x + 2) will be:A. x2 + 4 B. x2 + 4x - 4 C. x2 – 4
    1. answers icon 1 answer
  3. Solve each of the following equations by first expanding the brackets.a) 4(5 - b) = 18 b) 2(1 - m) = 13 c) 5(3 - x) = 19
    1. answers icon 1 answer
more similar questions